Phase II Study of Axalimogene Filolisbac (ADXS-HPV) for Platinum-Refractory Cervical Carcinoma: an NRG Oncology/Gynecologic Oncology Group Study - Huh, Warner K. (Gynecol Oncol, 2020)
OBJECTIVE: Women with persistent, recurrent, and/or metastatic cervical cancer have a poor prognosis. Even with the availability of cisplatin plus paclitaxel and bevacizumab, median overall survival (OS) is only 17.0 months, with median post-progression survival of approximately seven months. We studied the therapeutic vaccine, Axalimogene filolisbac (ADXS-HPV), in women who had progressed following at least one prior line of therapy (Gynecologic Oncology Group protocol 265/NCT01266460). METHODS: Volunteers ≥18 years with advanced cervical cancer and GOG performance status score of 0 or 1 were eligible for participation in this 2-stage, phase II trial. In stage 1, women received up to three doses of ADXS-HPV (1×10(9) colony-forming units in 250 mL IV over 15 minutes every 28 days) and were monitored for tumor progression. In stage 2, women were treated until progression, intolerable adverse events (AEs), or voluntary withdrawal of consent. Co-primary endpoints were safety and proportion of volunteers surviving ≥12 months. An estimated, combined (stages 1+2) 12-month OS of 35% was calculated from historical GOG cohorts to declare ADXS-HPV sufficiently active in this platinum-pretreated population. Secondary endpoints were OS and progression-free survival (PFS). RESULTS: Among 50 evaluable volunteers, the 12-month OS was 38% (n=19). Median OS was 6.1 months (95% CI: 4.3–12.1) and median PFS was 2.8 months (95% CI: 2.6–3.0). The most common treatment-related AEs were fatigue, chills, fever, nausea, and anemia. The majority of AEs were grade 1 or 2 and resolved spontaneously or with appropriate treatment. CONCLUSION: At the dose and schedule studied, ADXS-HPV immunotherapy was tolerable and met the protocol-specified benchmark for activity required to warrant further investigation in volunteers with cervical carcinoma.